Eating Disorders among Jordanian Women : A Collective Case Study - Shuriquie, Nasser; Abd Alhamid, Mona (اتحاد الاطباء النفسانيين العرب, 2005)
الدلائل من الدراسات العربية والغير غربية الأخيرة أفادت أن أمراض اضطرابات الطعام لا تقتصر على المجتمعات الغربية. هدفت هذه الدراسة إلى إجراء متابعة لخمس سيدات أردنيات عانين من أمراض اضطرابات الطعام وتلقين العلاج المعرفي المحفز للدافعية والعلاج الدوائي لمدة خمس سنوات. استعمل لهذا الغرض دراسة بحثية تجميعية لخمس حالات من اضطرابات الطعام لمحاولة معرفة العوامل الإيجابية والعوامل السلبية المؤثرة على مسيرة المرض. Evidence from recent Arabic and other non-western studies indicates that Eating Disorders are not restricted to the western societies. This study aimed to carry out a follow up of Jordanian girls who suffered from eating disorders and received Motivation Enhancement Therapy and medical treatment during most of a 5 year period. Collective case study methodol-ogy was used to examine 5 Eating disorders cases and to discuss the good and the poor prognostic factors that may have affected the course of their illness.
Keywords: الطعام -- الإضطرابات النفسية -- العلاج -- النساء ، الأردن